2019
DOI: 10.1101/635854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peptidoglycan associated cyclic lipopeptide disrupts viral infectivity

Abstract: 1Enteric viruses exploit bacterial components including lipopolysaccharides (LPS) and 2 peptidoglycan (PG) to facilitate infection in humans. With origins in the bat enteric system, we 3 wondered if severe acute respiratory syndrome-coronavirus (SARS-CoV) or Middle East 4 respiratory syndrome-CoV (MERS-CoV) also use bacterial components to modulate infectivity. 5To test this question, we incubated CoVs with LPS and PG and evaluated infectivity finding no 6 change following LPS treatment. However, PG from B. su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…As discussed above, there is emerging evidence suggesting suppression of influenza virus infection by bacteria. Additionally, it is shown that a peptidoglycan produced by the Gram‐positive bacterium Bacillus subtilis, a member of phylum Firmicutes, can abrogate infectivity of SARS‐CoV and Middle Eastern respiratory syndrome coronavirus (MERS‐CoV) [30]. Thus, although the interaction of SARS‐CoV‐2 and URT commensal microbiota should yet be investigated, it is reasonable to assume such an interaction plays a role in pathogenesis of the virus.…”
Section: The Interaction Of Bacteria and Influenza Virusmentioning
confidence: 99%
“…As discussed above, there is emerging evidence suggesting suppression of influenza virus infection by bacteria. Additionally, it is shown that a peptidoglycan produced by the Gram‐positive bacterium Bacillus subtilis, a member of phylum Firmicutes, can abrogate infectivity of SARS‐CoV and Middle Eastern respiratory syndrome coronavirus (MERS‐CoV) [30]. Thus, although the interaction of SARS‐CoV‐2 and URT commensal microbiota should yet be investigated, it is reasonable to assume such an interaction plays a role in pathogenesis of the virus.…”
Section: The Interaction Of Bacteria and Influenza Virusmentioning
confidence: 99%
“…Because we observe significant reductions in LACV titers with valinomycin treatment, we hypothesized that valinomycin might be directly affecting cellular processes to reduce virus infection. Nonetheless, valinomycin is a cyclic peptide and could potentially directly inactivate viral particles, as seen previously 20 . To test whether valinomycin directly reduced virus infectivity, we directly incubated LACV with 2 µM valinomycin for 24h and directly titered the surviving virus at regular intervals.…”
Section: Resultsmentioning
confidence: 80%
“…ZIKV, LACV, and, KEYV were obtained from Biodefense and Emerging Infections (BEI) Research Resources. HCoV-229E and MERS-CoV were propagated and quantitated via standard methods as previously described 20 .For all infections, drug was maintained throughout infection as designated. Viral stocks were maintained at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is also effective against many other viruses, such as influenza A (strains H1N1 and H3N2), Ebola and Zika. The usage of B. subtilis peptidoglycans reduces infectivity of CoV viruses (Johnson et al 2019 ). In China, Bacillus subtilis , Bacillus licheniformis and Bacillus cereus are ingested by adults, infants and newborns to relieve diarrhoea and build healthy intestinal microbiota.…”
Section: Microbiome As a Barrier To Virus Infectionmentioning
confidence: 99%